Protective Factors Modulate the Risk of Beta Amyloid in Alzheimer’s Disease - Bin Zhou; Kenichiro Tanabe; Shinsuke Kojima; Satoshi Teramukai; Masanori Fukushima; The Alzheimer’s Disease Neuroimaging Initiative (Behavioural Neurology)
Aim. To identify the factors protecting Abeta-positive subjects with normal cognition (NC) or mild cognitive impairment (MCI) from conversion to Alzheimer’s disease (AD). Methods. Subjects with MCI in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database, with baseline data for neuropsychological tests, brain beta amyloid (Abeta), magnetic resonance imaging (MRI), APOE genotyping, and 18F-FDG-PET (FDG), were included for analysis. Results. Elevated brain amyloid was associated with a higher risk of conversion from MCI to AD (41.5%) relative to Abeta levels of <1.231 (5.5%) but was not associated with conversion from NC to AD (0.0 vs. 1.4%). In the multivariate Cox regression analyses, elevated Abeta increased the risk of AD, while higher whole-brain cerebral glucose metabolism (CGM) assessed by FDG decreased the risk of AD in subjects with the same amount of Abeta. Even in the patients with heavily elevated brain amyloid, those with FDG>5.946 had a lower risk of AD. ApoE4 carrier status did not influence the protective effect. Conclusion. Higher average CGM based on FDG modified the progression to AD, indicating a protective function. The results suggest that the inclusion of this CGM measured by FDG would enrich clinical trial design and that increasing CGM along with the use of anti-Abeta agents might be a potential prevention strategy for AD.